Women writers dramatized : a calendar of performances from narrative works published in English to 1900 - Bolton, H. Philip (Bolton, H. Philip. Novels on stage, 2000)
A calendar of performances, consisting of some 2700 entries, of dramatizations by predominantly English but also eminent French women writers up to the end of the 19th century. These include Louisa May Alcott, Jane Austen, the Brontes, Aphra Behn, Ouida, and George Sand.